STRATEGI KESANTUNAN POSITIF DALAM BASA-BASI BANJAR - Rissari Yayuk (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2016)
This research is about positive politeness strategy in Banjar’s small talk. It analyzes 1) forms of Banjar’s small talk and 2) the positive politeness strategy in Banjar’s small talk. The purpose of this research is to describe 1) forms of Banjar’s small talk and 2) the positive politeness strategy in Banjar’s small talk. Techniques used in the data collection are field technique, recording, and documentation in order to obtain the spoken and written data. The data were taken from the direct speech of Banjar people in Sekumpul Sub-district, Sungai Kacang Village, in January—June 2015. The small talk used involves the settings of rice fields, streets, and inside or outside houses in order to tell something, ask for permission, and invite someone. This small talk aims to enhance closeness and respect each other. Based on the data analysis, the most dominant positive politeness strategy used is the strategy that engages the hearer in the speaker’s activity.